2013
DOI: 10.1016/j.bpj.2013.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Induced Acetylcholine Receptor Clusters Inhabit Liquid-Ordered and Liquid-Disordered Domains

Abstract: The distribution of nicotinic acetylcholine receptor (AChR) clusters at the cell membrane was studied in CHO-K1/A5 cells using fluorescence microscopy. Di-4-ANEPPDHQ, a fluorescent probe that differentiates between liquid-ordered (Lo) and liquid-disordered (Ld) phases in model membranes, was used in combination with monoclonal anti-AChR antibody labeling of live cells, which induces AChR clustering. The so-called generalized polarization (GP) of di-4-ANEPPDHQ was measured in regions of the cell-surface membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Together with Toshihide Kobayashi we employed fPEGcholesterol to follow the dynamics of cholesterol internalization and to test whether nAChR endocytosis followed the same route. Most of the internalized receptor followed a pathway different from that of fPEG-cholesterol (Kamerbeek et al, 2013), in agreement with our early studies with Satyajit Mayor showing that the receptor utilized a RAC-dependent, clathrin-and dynamin-independent endocytic route (Kumari et al, 2008).…”
Section: Fluorescent Cholesterol Sensors and Membrane Probessupporting
confidence: 92%
See 1 more Smart Citation
“…Together with Toshihide Kobayashi we employed fPEGcholesterol to follow the dynamics of cholesterol internalization and to test whether nAChR endocytosis followed the same route. Most of the internalized receptor followed a pathway different from that of fPEG-cholesterol (Kamerbeek et al, 2013), in agreement with our early studies with Satyajit Mayor showing that the receptor utilized a RAC-dependent, clathrin-and dynamin-independent endocytic route (Kumari et al, 2008).…”
Section: Fluorescent Cholesterol Sensors and Membrane Probessupporting
confidence: 92%
“…In parallel, we used a dual-channel recording setup to measure di-4-ANEPPDHQ GP in different regions of the plasma membrane ( Figure 1 ). The nAChR showed a punctiform distribution in both Ld and Lo domains ( Kamerbeek et al, 2013 ). We observed a decrease in di-4-ANEPDHQ GP values upon cholesterol depletion, a change that was correlated with the diminution of nAChR aggregates associated with Lo domains ( Figure 1 ).…”
Section: Exploring the Physico-chemical Properties Of The Nachr Lipid...mentioning
confidence: 99%
“…Furthermore, Chol depletion affects the maintenance of the nAChR in the plasma membrane by several mechanisms. Treatments of cells with methyl-β-cyclodextrin, which extracts Chol from the membrane, enhanced nAChR internalization by endocytosis with a marked decrease of the number of nAChR domains, concomitantly with a gain-of-function of the remaining nAChR (Borroni et al, 2007; Borroni and Barrantes, 2011; Kamerbeek et al, 2013). Furthermore, chronic treatments with mevinolin, an inhibitor of 3-hydroxy-3-methyl-glutaryl-CoA reductase and hence of Chol synthesis, inhibited the trafficking of the receptor toward the membrane surface, which caused low nAChR cell-surface expression, and increased the intracellular nAChR pools (Pediconi et al, 2004).…”
Section: Nachr and Membrane Lipidsmentioning
confidence: 99%
“…An increase in α4 nAChR protein stability may explain the increase observed here. nAChRs are very sensitive to membrane cholesterol levels; ion translocation properties, membrane domain localization, rate and mechanism of internalization, and exocytic trafficking are strongly dependent on membrane cholesterol in muscle nAChR [ 13 , 14 , 15 , 16 , 19 ]. The results presented in this paper indicate that the cholesterol dependence may be a hallmark not only of the muscle-type nAChR but of the entire nAChR family.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol in particular is necessary for the maintenance of nAChRs at the plasmalemma and for ion translocation [ 4 ]. Previous studies have shown that cholesterol levels modulate the trafficking, membrane domain localization, and function of muscle-type nAChR heterologously expressed in CHO-K1/A5 cells and in endogenously expressed nAChR in C2C12 myotubes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Little is known, however, on the effects of cholesterol modulation on neuronal nAChR.…”
Section: Introductionmentioning
confidence: 99%